Audrey Ancell: capstone - Ancell, Audrey, artist (Colorado State University. Libraries, 2015)
The artist's statement: I find a great deal of inspiration in science and technology, along with the positive and negative implications of these on people and the natural world. There is something very beautiful about the constant search for truth, the wonder and awe at the world. We want to understand it on every level. We want to deconstruct it down to its most basic elements, and then reassemble it again so that it makes sense. I use this same basic idea in my art. I am always searching for answers, questioning what I see and think. It grows as I do, it is constantly evolving. It is always trying to prove itself wrong in its most sure state. It is life.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.